Metaverse platform ecosystems - Sofia Marlena Schöbel; Jan Marco Leimeister (Electronic Markets, 2023)
Traditionally, the metaverse has been defined as a virtual reality space in which users can interact with a computer-generated environment and other users. Nowadays, it is much more than that—the metaverse can be described as a variety of digital platforms and ecosystems, with each ecosystem as an independent universe with its own material, complementors, and functionalities. Creating metaverse ecosystems and integrated platforms results in different roles and responsibilities for complementors, consumers, platform owners, and orchestrators. The term metaverse platforms is further structured and clarified by four perspectives: innovation, production, transaction, and social interaction. Consequently, this fundamental~paper defines it as: "A Metaverse is a massively scaled and interoperable meta-ecosystem of other digital ecosystems of real-time rendered 3D virtual worlds which can be experienced synchronously and persistently by an unlimited number of complementors and consumers with an increased user experience caused by a creativity-guided co-creation of goods managed by orchestrators and supported by platform owners." Consequently, the metaverse offers vast opportunities for digital innovations beyond traditional social media or computer games and creates new infrastructures for add-on innovations in all areas of the digital economy.
Keywords: M21; 620; Metaverse; Platform; Ecosystem